Analysing Real Exchange Rate Effects on the Trade Balance in South Africa - Mokgokong, Moloko Kholofelo; Choga, Ireen (International Journal of Economics and Financial Issues, 2024)
For years, policymakers and economists have been researching the significance of the native currency value versus other currencies in favouring the country’s trade balance and total. Therefore, this study investigates the impact of the real exchange rate change on the trade balance in South Africa. The study used annual time series data from 1980 through 2022. This study used the ARDL technique to analyse data. Variables used in this study include the trade balance, real exchange rate, terms of trade, money supply, South Africa’s gross domestic product, and the Chinese gross domestic product. Bounds tests showed that the variables are cointegrated. According to the empirical findings, the real exchange rates have significantly influenced the trade balance positively in the short run but in the long run, have a negative significant influence on the trade balance. The terms of trade have a positive significant influence on the trade balance in the short run, but it appears to be positively significant in the long run. The money supply in the short run has an insignificant negative relationship with the trade balance but in the long run, has a significant positive relationship with the trade balance. The SA gross domestic product has a significant negative impact on the trade balance both in the short and long run. Lastly, the Chinese gross domestic product has a negative insignificant relationship with the trade balance in the short. However, in the long run, it has a positive significant relationship with the trade balance. This proves that a rise in Chinese GDP, as a proxy for foreign economic activity, boosts South African exports to the rest of the world in the long term. As a result, the trade balance improves as China imports minerals from South Africa for production purposes. The dependence on currency depreciation to enhance trade in South Africa can improve its trade balance, but it may also damage the economy due to the country’s reliance on imports. However, the advice to weaken the South African currency should not be so harsh as to have a negative impact on the importation of key capital goods critical to the growth and development of the South African economy. It is recommended that the government reduce demand for imported products and boost domestic manufacturing, which might lead to domestic products being exported. The central bank must also stabilize the currency to increase competitiveness by decreasing the overseas price of exports and increasing the cost of imports.